2011
DOI: 10.1111/j.2044-8333.2011.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Delays in attentional processing when viewing sexual imagery: The development and comparison of two measures

Abstract: Purpose. Critically important to effectively treating and managing sexual offending is the identification or validation of an offender's deviant sexual interests as the nature of their sexual interests is what demarcates repetitive sexual offenders from nonoffenders and lower risk offenders. As an alternative or verification to self-report or phallometric measures, focus has turned to attention-based measures. These measures assess sexual content-induced delay (SCID), a specific form of attentional bias associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Interestingly, additional analysis showed that the longer subjects viewed sexual distractors, the longer the RT in the mental rotation task, if an adult sexual distractor was presented (r=0.513, p<0.001). This result supports the theory of the SCID at the eye movement level [63]. The association of RT in our cognitive task and time of watching the sexually relevant distractors, i.e., the relative fixation time, indicates that the emotional state (elicited by viewing sexually relevant stimuli) could be the cause of the attentional bias and the subsequent delayed task processing.…”
Section: Measurement Of Sexual Interest Under Cognitive Load -Eye Movsupporting
confidence: 88%
“…Interestingly, additional analysis showed that the longer subjects viewed sexual distractors, the longer the RT in the mental rotation task, if an adult sexual distractor was presented (r=0.513, p<0.001). This result supports the theory of the SCID at the eye movement level [63]. The association of RT in our cognitive task and time of watching the sexually relevant distractors, i.e., the relative fixation time, indicates that the emotional state (elicited by viewing sexually relevant stimuli) could be the cause of the attentional bias and the subsequent delayed task processing.…”
Section: Measurement Of Sexual Interest Under Cognitive Load -Eye Movsupporting
confidence: 88%
“…Novel methods attempting to examine cognitions and/or cognitive components of deviant sexual interest include Implicit Association Tests (Banse, Schmidt, & Clarbour, 2010;Brown, Gray, & Snowden, 2009;Gray, Brown, MacCulloch, Smith, & Snowden, 2005;Mihailides, Devilly, & Ward, 2004;Nunes, Firestone, & Baldwin, 2007;Ó Ciardha & Gormley, 2009;Steffens, Yundina, & Panning, 2008), choice reaction time tests (Giotakos, 2005;Gress, 2008;Mokros, Dombert, Osterheider, Zappalà, & Santtila, 2010), modified Stroop tasks (Ó Ciardha & Gormley, in press;Price & Hanson, 2007;Smith & Waterman, 2004), rapid serial visual presentation tasks Keown, Gannon, & Ward, 2010), Implicit Relational Assessment Procedures (Dawson, Barnes-Holmes, Gresswell, Hart, & Gore, 2009) and lexical decision tasks (Blake & Gannon, 2010;Keown, Gannon, & Ward, 2008) . The majority of these have focused on the simpler-relatively speaking-task of measuring sexual interest.…”
Section: Differences Between Child Molesters and Othersmentioning
confidence: 99%
“…As with the P-MST, a systematic slowing down of reaction times to a given category of stimulus is interpreted as indicating an attentional bias towards this stimulus category. This task has been used several times to attempt to measure sexual interest generally (Santtila, et al, 2009;Wright & Adams, 1994, 1999 and also to attempt to measure sexual interest in offenders (Giotakos, 2005;Gress, 2011;Mokros, et al, 2010). Adams (1994, 1999) demonstrated that the CRT paradigm could be used to correctly classify gay and straight men and women.…”
Section: Introductionmentioning
confidence: 99%